Aktivitas Gel Kombinasi Ekstrak Rimpang Kunyit dan Gel Gamat Terhadap Penyembuhan Luka - Lina Noviyanti Sutardi; Aulia Andi Mustika; Andriyanto; Rahmawati Januar; Aisyah Nurfitria Ayumi (Acta VETERINARIA Indonesiana, 2022)
The purpose of this study is to determine the efficacy of a combination gel of turmeric extract and gamat gel as a medicament to accelerate the healing process of incisions which is easy to apply, practical, and effective in white Sprague-Dawley rats based on anatomical pathology observations. A total of 30 rats used were divided into a randomized design with 5 treatment groups. The skin of the rats was incised on the left or right stomach along 3 cm. Each wound was then treated with a different treatment. The treatments given were negative control (placebo gel), combination gel of turmeric extract and gamat gel with variated concentrations (0.5%, 1%, 2%), and positive control (commercial ointment contained Centella asiatica 15%). Anatomical pathology were observed every day for 21 days. Observations are made by comparing the changes that occur descriptively during the healing process. The parameters observed were wound length, wound depth, wound edge, exudate type, skin color, and the presence of hair. The results showed that the group that was given a combination gel and positive control had the better effect on the acceleration of wound healing compared to the negative control which was only given placebo gel, this shows that the wound healing process is accelerated by giving a combination gel of turmeric extract and gamat gel. The 2% concentration group gave better healing results compared to the 0.5% and 1% concentration groups. Keywords: Extract, gamat, gel, turmeric, wound healing.